THE EFFECT OF STORYTELLING IN A PLAY THERAPY ON ANXIETY LEVEL IN PRE-SCHOOL CHILDREN DURING HOSPITALIZATION IN THE GENERAL HOSPITAL OF BUTON - Yati, Mimi; Wahyuni, Sri; Islaeli, Islaeli (Public Health of Indonesia, 2017)
Background: Anxiety is one of the psychical stresses experienced by children during hospitalization. A storytelling in a play therapy is considered effective in reducing anxiety.Objective: This study aims to determine the effect of storytelling in a play therapy on anxiety level in pre-school children during hospitalization in the general hospital of Buton.Methods: This was a quasy-experimental study with pretest-posttest control group design. There were 30 pre-school children selected in this study using accidental sampling, with 15 assigned in each group. The Pre School - Spence Children's Anxiety Scale (SCAS) was used to measure anxiety in pre-school children. Wilcoxon matched paired test was used to analyze the data. Results: Findings showed that the mean of anxiety level in the intervention group in pretest was 42 and in posttest was 31.53. Wilcoxon matched paired test showed p-value 0.003 (<0.05), which indicated that there was a statistically significant effect of storytelling on the level of anxiety in pre-school children.Conclusions: There is a significant influence of storytelling in a play therapy on anxiety levels in pre school children during hospitalization. It is suggested that this intervention could be applied as a nursing intervention to reduce anxiety in children.